Detecting red flags of corporate financial statement frauds using beneish m score model in sri lanka - Mudith Sujeewa, G.M.; Pubudu Kawshalya, M.D. (International Journal of Accounting & Business Finance, 2020)
Financial statement fraud is one of the major concerns in the modern business world. Detecting financial statement fraud is very challenging task and requires thorough knowledge about the nature of fraud, how it can be committed and concealed. The purpose of the study is to identify the red flags of financial statement frauds applying Benish M Score model. It is found that, in each year (2013-2019) considered for the study, there are companies with a Beneish M Score of greater than -2.22, which can be gauged for possible manipulations on those financial statements. Paired sample t-test analysis is showen that, DSRI (Days’ Sales in Receivables Index), GMI (Gross Margin Index), SGI (Sales Growth Index) LVGI (Leverage Index), TATA (Total Accruals to Total Assets) out of eight ratios occupied in the Beniesh model are significantly different between manipulated and non-manipulated firms. Therefore, it is recommended that Benish M Score model can be used as a risk assessment tool to recognize the red flags of possible fiancial statemet frauds in business entities in Sri Lanka. This paper aims at broadening knowledge of External Auditors, Forensic Accountants, Accountants, Senior Managers, Regulators and other stakeholders in detecting red flags of financial statement frauds in Sri Lanka.
Keywords: Benish M Score Model; Financial Statement Fraud; Days’ Sales in Receivables Index; Gross Margin Index; Sales Growth Index; Leverage Index; Total Accruals to Total Assets